The Importance of Self-regulation and Co-regulation in the New Digital Audiovisual Market - Saldaña,Mercedes Muñoz (2015)
On April 5, 2013, under the Plan for Children and Adolescents 2013-2016, the adoption of new Self-regulatory codes on audiovisual content on the part of the media was announced. On January 14, 2013 the first Co-regulation Agreement applicable to broadcast advertising was signed by radio service providers. Proper assessment of instituting these codes requires previous analysis of more than one issue, one being the reason for applying these instruments to the audiovisual market, and another being an analysis and evaluation regarding the characteristics of the digital audiovisual market. This study delves deep into said aspects for the purpose of evaluating the future application of self-regulation and of co-regulation to the media sector within Spain.